2020
DOI: 10.1088/2632-2153/ab6ac4
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning the computational cost of quantum chemistry

Abstract: Computational quantum mechanics based molecular and materials design campaigns consume increasingly more high-performance compute resources, making improved job scheduling efficiency desirable in order to reduce carbon footprint or wasteful spending. We introduce quantum machine learning (QML) models of the computational cost of common quantum chemistry tasks. For single point, geometry optimization, and transition state calculations the out of sample prediction error of QML models of wall times decays systema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 72 publications
0
49
0
1
Order By: Relevance
“…For the QML models of the computational cost of typical quantum chemistry computations (measured by the CPU wall time), Heinen et al. reported the QMt data set, 380 consisting of timings of various tasks (single point energy, geometry optimization, and transition state search) for thousands of QM9 molecules at several levels of theory including B3LYP/def2-TZVP, MP2/6-311G(d), LCCSD(T)/VTZ-F12, CASSCF/VDZ-F12, and MRCISD+Q-F12/VDZ-F12.…”
Section: Data Setsmentioning
confidence: 99%
“…For the QML models of the computational cost of typical quantum chemistry computations (measured by the CPU wall time), Heinen et al. reported the QMt data set, 380 consisting of timings of various tasks (single point energy, geometry optimization, and transition state search) for thousands of QM9 molecules at several levels of theory including B3LYP/def2-TZVP, MP2/6-311G(d), LCCSD(T)/VTZ-F12, CASSCF/VDZ-F12, and MRCISD+Q-F12/VDZ-F12.…”
Section: Data Setsmentioning
confidence: 99%
“…Como mostrado na seção anterior, o MLé uma ferramenta matemática e estatística, podendo então ser aplicada aos mais diferentes tipos de problemas. Nesse sentido, não apenas os problemas científicos em si podem ser estudados, como também tarefas que usualmente não são estudadas mas que existem dados disponíveis, tal como estimar o tempo que um processo computacional vai levar, permitindo sua otimização [47]. No contexto específico de materais, o ML pode ser usado para a descoberta, design e otimização de propriedades tanto partindo de dados experimentais [48][49][50] como de simulação, e esta pode ser atomística (clássica) ou ab initio (quântica).…”
Section: Aplicações Em Materiais: Descoberta E Designunclassified
“…However, as far as we know, there is nearly no related work concerning to the prediction of computation cost in the field of quantum chemistry, except in the area of quantum machine learning (QML) models that very recently introduced by Heinen and co-workers. 14 They demonstrated that QML-based wall time predictions significantly improve job scheduling efficiency by reducing CPU time overhead ranging from 10 to 90%. Until now, there has been no universal solution for predicting the computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…The current QML solution is restricted to a specified computational approach and specified parameters, and training of a corresponding ML model is essential before practical predictions. 14 However, it may not be convenient for training the specific model each time before the practical calculations. Thus, generalization ability should be one of the essential elements for an universal solution when predicting the computational cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation